2016
DOI: 10.1590/1807-3107bor-2016.vol30.0015
|View full text |Cite
|
Sign up to set email alerts
|

Parafunctional habits are associated cumulatively to painful temporomandibular disorders in adolescents

Abstract: This cross-sectional study was designed to evaluate the effect of sleep bruxism, awake bruxism and parafunctional habits, both separately and cumulatively, on the likelihood of adolescents to present painful TMD. The study was conducted on a sample of 1,094 adolescents (aged 12-14). The presence of painful TMD was assessed using the Research Diagnostic Criteria for Temporomandibular Disorders, Axis I. Data on sleep bruxism, awake bruxism and parafunctional habits (nail/pen/pencil/lip/cheek biting, resting one'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 23 publications
(36 reference statements)
6
29
3
4
Order By: Relevance
“…Similarly, Vanderas and co‐workers reported an association between muscle tenderness and oral parafunction such as grinding, clenching and lip biting in children. These findings are also in accordance with what is reported in adults, suggesting that parafunctional activities might represent a risk factor for TMD‐pain and in general for TMD in different age groups …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, Vanderas and co‐workers reported an association between muscle tenderness and oral parafunction such as grinding, clenching and lip biting in children. These findings are also in accordance with what is reported in adults, suggesting that parafunctional activities might represent a risk factor for TMD‐pain and in general for TMD in different age groups …”
Section: Discussionsupporting
confidence: 92%
“…in accordance with what is reported in adults, suggesting that parafunctional activities might represent a risk factor for TMD-pain 37 and in general for TMD 35,38 in different age groups. 38 In the present study, a significant association between negative OVB and TMD-pain was also found.…”
Section: Discussionsupporting
confidence: 91%
“…1,6 A cross-sectional study showed that muscle activity during sleep was a good predictor for painful TMD in adolescents. 7 However, other studies have found that low levels of SB are more correlated with TMD than higher levels of SB. 8,9 It was also previously reported that as much as 70% of TMD patients with myofascial pain also showed evidences of rhythmic masticatory muscle activity (RMMA) upon clinical examination and ambulatory sleep recordings.…”
Section: Introductionmentioning
confidence: 94%
“…Some limitations of this review. We used self-reporting questionnaires not referred in the international literature, although recent publications have used a similar methodology to investigate parafunctional habits in adolescents 32,33 . The sample was not representative of the population which prevents from generalizing the results.…”
Section: Discussionmentioning
confidence: 99%